Persepsi Mahasiswa Tentang Ekstrakurikuler English Camp Dalam Meningkatkan Kemahiran Berbahasa Inggris - Adi, Sugeng Susilo; Wijaya, Rahmad Adi (Inovasi: Jurnal Diklat Keagamaan, 2022)
This study aims at describing students’ perception about English Camp for the first-year student of English Education Study Program at Universitas Brawijaya on enhancing English proficiency through the three domains of learning. English Camp is innovation from English Education Study Program that begin from 2016. But, the perception of students who had joined English Camp are still unknown. The type of this study is descriptive, using quantitative approach. Data were gained from student answer on questionnaire that they had fulfilled. The sampling technique used in this study was accidental sampling. Subjects in this study were 40 students from a total of English Education student batch of 2018 at Universitas Brawijaya. This study using questionnaire that had been validated by the expert as the instrument. The questionnaire uses Likert scale where there are two forms of statements, positive and negative statements. The results show that almost all of respondent give positive perception that English Camp can enhance their English proficiency through the three domains of learning: cognitive, affective and psychomotor. Almost all of student show their agreement based on the 10 statements through questionnaire the researcher provide. The conclusion of this study is that almost all students give positive perception. It refers to the three domains of learning by Bloom. From the three domains, it shows a positive perception in each domain. This indicates that students get enhanced in English proficiency by following English Camp.